Analisis Financial Distress dengan Menggunakan Metode Springate Pada Perusahaan Sektor Pariwisata dan Transportasi Yang Terdaftar Di BEI Pada Tahun 2018– 2020 - Nashohah, Dalilatun; Barizi, Toha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this research is to find out which companies have indications of bankruptcy in the tourism and transportation sectors, both of which are experiencing a slump after the outbreak of the covid-19 pandemic. This research is a descriptive quantitative study using secondary data. The sample in this study was 51 companies consisting of 20 companies registered in the tourism sector and 31 companies registered in the transportation sector companies. This study found that in the tourism sector, on average, it was in the bankrupt category, there were only 6 (30%) companies in the safe category with specifications 4 companies were in the healthy category and 2 companies were in the healthy category with the threat of bankruptcy from a total of 20 listed companies. While the remaining 14 (70%) companies are in the bankrupt category. Likewise, the tourism sector, on average, is in the bankrupt category. The total number of companies in the tourism sector is 31 companies, only 4 companies are included in the healthy category. While the remaining 28 companies are in the unhealthy category (bankrupt). This means that as many as 90% experienced bankruptcy while only the remaining 10% experienced a healthy condition